Commercialization of R&D: The Role of Science Parks - Clark, Woodrow W. (Marketing & Menedzsment, 2019)
Business development in any country has become an important topic for not only economic but also political reasons. For transitional economies, it has become even more significant due to the need to move rapidly into the modem economic mainstream while building on traditional strengths and combating the restrictive recent history of control economic systems. With that economic perspective or paradigm in mind, a science park must be a combination of groups and organizations which interact with one another in other to create and gmw businesses. A key component or actor in that interaction is the government. A variety of areas for government interaction are discussed ending with the example from Denmark of NOVI Science Park.